Dodal Lala: Pemanfaatan ampas pembuatan minyak sumbawa sebagai bahan pangan - Hakim, Aliefman; Siahaan, Jackson; Loka, I Nyoman; Apriani, Senly; Sapitri, Riska Dia (Universitas Mataram, 2025)
Sumbawa oil is a traditional medicine renowned for its efficacy in treating various ailments. This oil continues to be produced today using a variety of spices. Most of the production residue comes from coconut milk curd (blondo). The caramelization process of blondo produces a sweet flavor. This residue is then processed into high-value snack products. Dodal is tested organoleptically to ensure the taste, color, and aroma of the spices in the product are pleasant to consume. This testing is conducted to ensure the quality of the dodal due to high-temperature heating. Dodal is packaged in ready-to-eat packaging, making it convenient for use and storage. This processing ensures that the oil residue (in the form of dodal) has a long shelf life for extended storage and adds economic value to the local community.